Hemorrhagic stroke: a diagnosis guided by visual field findings - Riese, Nicole Auchter; Bailey, Melissa Annette (Canadian Journal of Optometry, 2021)
This case report outlines a patient with a hemorrhagic stroke who presented to the eye clinic with visual field loss, which the patient interpreted as blur, and a severe headache. The visual field loss consisted of an incomplete homonymous hemianopsia with an absolute superior defect, which corresponds well to the right sided temporal lobe hemorrhage found on head computed tomography (CT) scan. This case highlights the importance of all eye care providers recognizing stroke symptoms and understanding referral timelines and protocols as well as the high predictive value of visual fields.